2017
DOI: 10.1007/s00280-017-3309-6
|View full text |Cite|
|
Sign up to set email alerts
|

Population pharmacokinetic modelling of doxorubicin and doxorubicinol in children with cancer: is there a relationship with cardiac troponin profiles?

Abstract: Prior anthracycline exposure increased baseline cTnI in a dose-dependent manner, consistent with the known cumulative risk of anthracycline exposure-induced cardiotoxicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(36 citation statements)
references
References 31 publications
1
34
1
Order By: Relevance
“…TnI is more feasible than the other cardiac troponins for early CIC diagnosis due to its kinetic curve [18], but the exact dynamic of troponin release into bloodstream is not well known [5,12,19]. Although several papers have been published regarding CIC evaluation by troponin measurements, there are only a few studies on this subject in pediatric ALL setting [20][21][22][23][24][25][26][27][28][29]. Different groups monitored large cohorts of children with ALL and concluded that TnI was predictable for myocardial injury [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…TnI is more feasible than the other cardiac troponins for early CIC diagnosis due to its kinetic curve [18], but the exact dynamic of troponin release into bloodstream is not well known [5,12,19]. Although several papers have been published regarding CIC evaluation by troponin measurements, there are only a few studies on this subject in pediatric ALL setting [20][21][22][23][24][25][26][27][28][29]. Different groups monitored large cohorts of children with ALL and concluded that TnI was predictable for myocardial injury [20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Different groups monitored large cohorts of children with ALL and concluded that TnI was predictable for myocardial injury [20][21][22]. There is evidence that TnI level is correlated with AC treatment in a dose-dependent manner [23][24] and the increase occurs 2-4 weeks after administration [25] but there are studies in which no changes in the troponin values during AC treatment were found [26][27][28][29]. In our study, in children with ALL receiving low CD of AC, TnI increased in direct proportion with the number of doses (p<0.001), only one hour after the administration.…”
Section: Discussionmentioning
confidence: 99%
“…In 19 children (3–15 years) who underwent sparse sampling up to 168 hours postinfusion over multiple doxorubicin doses, Kunarajah et al 60 also reported a mean doxorubicin clearance similar to that of adults (58.7 L/h/1.8m 2 ) with a significant effect of BSA scaling and age (as a power function) on doxorubicin clearance, and of BSA scaling on volume of distribution. Doxorubicin clearance in the very young is consistently reported to be significantly lower than in older children, 59,60,67 even when adjusted for BSA, with calculated values for a neonate 60 of 9.1 L/h/m 2 and 12.0 L/h/m 2 67 compared to 29.0 and 24.1 L/h/m 2 in a 5 year old, respectively. Importantly, Voller et al 67 have proposed that whilst BSA adjusts clearance for body size, age further adjusts for the maturation of clearance pathways.…”
Section: Pharmacokinetic Modelsmentioning
confidence: 95%
“…Kunarajah and colleagues used an E max model to link combined plasma concentrations of doxorubicin (DXR) and its primary metabolite, doxorubicinol (DXR-ol), with the cardiac troponin index (cTnI) as a marker of cardiotoxicity in 17 children. 58 They were able to predict DXR and DXR-ol concentrations and cTnI after DXR dosing. They could also calculate the combined concentration of DXR and DXR-ol, which resulted in half-maximal cTnI increase.…”
Section: Clinical Perspectivementioning
confidence: 97%
“…Such equations can be easily rearranged to describe inhibition. Kunarajah and colleagues used an E max model to link combined plasma concentrations of doxorubicin (DXR) and its primary metabolite, doxorubicinol (DXR‐ol), with the cardiac troponin index (cTnI) as a marker of cardiotoxicity in 17 children . They were able to predict DXR and DXR‐ol concentrations and cTnI after DXR dosing.…”
Section: Clinical Perspectivementioning
confidence: 99%